2003
DOI: 10.1002/em.10135
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide and merbarone are clastogenic and aneugenic in the mouse bone marrow micronucleus test complemented by fluorescence in situ hybridization with the mouse minor satellite DNA probe

Abstract: The topoisomerase II (topo II) inhibitors etoposide (VP-16) and merbarone (MER) were investigated with the in vivo micronucleus test (MN test) combined with fluorescence in situ hybridization (FISH) using the mouse minor satellite DNA probe to discriminate MN of clastogenic and aneugenic origin. All experiments were performed with male (102/ElxC3H/El) F1 mice bred in the mouse colony of the GSF Research Center. The sample size per experimental group was five animals and 2,000 polychromatic erythrocytes (PCE) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
8
15
1
Order By: Relevance
“…It has been reported that merbarone is aneugenic as well as clastogenic [33]. In good agreement with our earlier reports on the effectiveness of different topo II inhibitors to induce endoreduplication [16,40], in the present investigation we have observed that merbarone also inhibits topo II catalytic activity in cultured Chinese hamster ovary AA8 cell line and induces endoreduplication under conditions where also DNA damage is induced.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been reported that merbarone is aneugenic as well as clastogenic [33]. In good agreement with our earlier reports on the effectiveness of different topo II inhibitors to induce endoreduplication [16,40], in the present investigation we have observed that merbarone also inhibits topo II catalytic activity in cultured Chinese hamster ovary AA8 cell line and induces endoreduplication under conditions where also DNA damage is induced.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, more recent investigations have shown that merbarone and the structurally related bisdioxopiperazines (ICRF-193, and ICRF-187) induced strong dose-dependent genotoxic effects in mammalian cells similar to those seen with the topo II poison etoposide. In addition, clastogenic effects could be seen in vivo in bone marrow erythrocytes from merbarone-treated mice [10,11,[30][31][32][33]. The striking difference between the numerous negative results and the latter has not been satisfactorily explained so far.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, micronucleus assays using human cultured somatic cells and mouse bone marrow cells have demonstrated that merbarone can induce both structural chromosome aberrations and aneuploidy [34,35]. Although the molecular mechanisms underlying the clastogenicity of merbarone 15 remain to be fully elucidated, the dysfunction of ooplasmic topo II by this agent may cause the torsional stress of DNA to accumulate in remodeled sperm chromatin, thereby generating DNA strand breaks.…”
Section: Discussionmentioning
confidence: 99%
“…The negative control groups received PBS only, while the positive control groups were injected intraperitoneally with either 2 mg/kg mitomycin C (MMC; Sigma) or 2 mg/kg colchicine (COL; Sigma). The doses for the positive controls were chosen by reference to earlier in vivo studies [Schriever-Schwemmer and Adler, 1994;Schriever-Schwemmer et al, 1997;Attia et al, 2003;Attia, 2007]. The doses of lomefloxacin were selected on the basis of their effectiveness in inducing chromosomal alterations in mouse bone marrow [Singh et al, 2003].…”
Section: Drugs and Chemicalsmentioning
confidence: 99%